2014
DOI: 10.4317/jced.51499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, etiology, diagnosis, treatment and complications of supernumerary teeth

Abstract: The aim of this article was to review the literature on supernumerary teeth, analyzing their prevalence, etiology, diagnosis, treatment and possible complications. An electronic search was made in the Pubmed-Medline database up to January 2014 using the key search terms “multiple supernumerary teeth” (n=279), “prevalence supernumerary teeth” (n=361), and “supernumerary teeth” (n=2412). In addition to the articles initially identified, others were included in the review proceeding from a manual search and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(178 citation statements)
references
References 30 publications
8
118
2
11
Order By: Relevance
“…While no other syndrome has been observed in a patient, it is rare that supernumerary teeth occur in abundance or in more than one quadrant [7,16,51]. Liu et al [52] identified a single supernumerary tooth in 72% of the cases, two in 27%, 3 and more in 0.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While no other syndrome has been observed in a patient, it is rare that supernumerary teeth occur in abundance or in more than one quadrant [7,16,51]. Liu et al [52] identified a single supernumerary tooth in 72% of the cases, two in 27%, 3 and more in 0.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Rudimentary teeth have conical and tubercular (molariform) sub-types [4,16,47,55]. In a study of 40 cases with distomolar teeth, Gündüz and Çelenk [8] observed smaller distomolars (rudimentary) in 75% of the cases and normal-looking ones (supplemental) in 25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next most frequent locations were maxillary third molar region (29.6%), mandibular third molar region (7%), mandibular premolar region (7%), maxillary premolar region (4.2%) and mandibular incisor region (4.2%). 17 The prevalence of supernumerary teeth is 0.3 -0.8% in deciduous dentition and 1.5 -3.5% in permanent dentition, 1,18,19 with higher incidence rate in males than females (incidence ratio of 2:1 6,9 or 4:1 12 ). This is in agreement with our case.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most accepted theory is the dental lamina hyperactivity theory which suggests that they are formed as a result of local, independent, conditioned hyperactivity of the dental lamina. However, the role of complex interactions among a variety of environmental and genetic factors has been postulated [2,12].…”
Section: Discussionmentioning
confidence: 99%